Analysis Simple Additive Weighting And Genetic Algorithm For Traffic Management System - Aziz, Abdul; Nasution, Surya Michrandi; Setianingsih, Casi (International Journal of Integrated Engineering, 2020)
Bandung Tourism is currently developing rapidly, where every year the number of tourist attractions has increased. The convenience provided by today's technology such as Google Maps is still lacking in helping tourists. Until now, software that is useful for determining the route by selecting tourist attractions is still small. The problem of tourists in making a tour include traffic jams, distances and tourist attractions to be visited. Application development to help find the best route is very much needed by tourists. The best route search optimization can be done using Genetic Algorithms. Genetic Algorithms are often used in determining the route because based on previous research it produces optimal results. Weighting for a path can be done using the Simple Additive Weighting Algorithm. In this study optimization of route selection is done in the hope that it can provide solutions to tourists in route selection.